Utilization of Pentalearner Media to Improve Understanding of The Concept of Pancasila Values in Pancasila Education Learning - Ganda, Ruth Ellyana; Ammy, Putri Maisyarah; Simarmata, Hotnida (STABN RADEN WIJAYA WONOGIRI, 2024)
This study aims to determine the Utilization of Pentalearner Media to Improve Understanding of the Concept of Pancasila Values in Pancasila Education Learning at Sd N 066055 Medan. This type of research is Classroom Action Research (CAR). Based on the results of classroom action research that has been carried out in two cycles in class III SDN 066055 Medan City, it can be concluded that the use of Pentalearner media is significantly able to improve the understanding of the concept of Pancasila values in students. The application of this media in the learning process of Pancasila Education is carried out through a contextual and interactive approach, namely with the Problem Based Learning (PBL) learning model and the Culturally Responsive Teaching approach, which is adjusted to the characteristics and learning needs of phase B students. Pentalearner media designed in the form of five learning sides is proven to be effective in encouraging active student involvement in learning activities. Students not only memorize the precepts of Pancasila, but are able to explain the meaning of each precept, identify behaviors that are in accordance with the values of Pancasila, recognize the national symbol and the figures who formulated Pancasila, and apply these values in everyday life. This is reflected in the increase in student learning outcomes from pre-action to cycle I, and further increased in cycle II. The average student score increased from 60.78 in the pre-test to 80 in the post-test of cycle I, and reached 90.26 in the post-test of cycle II. Classical completeness also increased from 52.63% in the pre-test to 94.73% at the end of cycle II. In addition, the average N-Gain value of 0.77 is included in the high category, which indicates the effectiveness of using this media.